Vocal behavior of false killer whale (Pseudorca crassidens) acoustic subgroups - Gruden, Pina; Barkley, Yvonne M.; McCullough, Jennifer L. K. (Frontiers in Marine Science, 2023)
Understanding the vocal behavior of cetaceans is an important component of many passive acoustic applications. This study quantifies the vocal behavior of acoustic subgroups of false killer whales (Pseudorca crassidens) from the Hawaiian Archipelago. The acoustic subgroups (N = 523) exhibit diverse vocal behavior that varies between encounters. Overall, 29% of acoustic subgroups only echolocate, 16% only whistle, and 55% emit both types of vocalizations. These results contribute important information for developing automated passive acoustic cetacean tracking, localization, and classification techniques, and thus, support future cetacean monitoring and assessment efforts.